Differential expression of cardiometabolic and inflammation markers and signaling pathways between overweight/obese Qatari adults with high and low plasma salivary α-amylase activity - Khalifa, Olfa; Al-Akl, Neyla S.; Arredouani, Abdelilah (Frontiers in Endocrinology, 2024)
The relationship between salivary α-amylase activity (sAAa) and susceptibility to cardiovascular disorders lacks a definitive consensus in available studies.To fill this knowledge gap, the present study endeavors to investigate this association among overweight/obese otherwise healthy Qatari adults. The study specifically categorizes participants based on their sAAa into high and low subgroups, aiming to provide a more comprehensive understanding of the potential link between sAAa levels and cardiovascular and inflammation markers in this population.Methods: Plasma samples of 264 Qatari overweight/obese (Ow/Ob) participants were used to quantify the sAAa and to profile the proteins germane to cardiovascular, cardiometabolic, metabolism, and organ damage in low sAAa (LsAAa) and high sAAa (HsAAa) subjects using the Olink technology. Comprehensive statistical tools as well as chemometric and enrichments analyses were used to identify differentially expressed proteins (DEPs) and their associated signalling pathways and cellular functions.Results: A total of ten DEPs were detected, among them five were upregulated (QPCT, LCN2, PON2, DPP7, CRKL) while five were down regulated in the LsAAa subgroup compared to the HsAAa subgroup (ARG1, CTSH, SERPINB6, OSMR, ALDH3A).Functional enrichment analysis highlighted several relevant signalling pathways and cellular functions enriched in the DEPs, including myocardial dysfunction, disorder of blood pressure, myocardial infraction, apoptosis of cardiomyocytes, hypertension, chronic inflammatory disorder, immunes-mediated inflammatory disease, inflammatory response, activation of leukocytes and activation of phagocytes.Our study unveils substantial alterations within numerous canonical pathways and cellular or molecular functions that bear relevance to cardiometabolic disorders among Ow/Ob Qatari adults exhibiting LsAAa and HsAAa in the plasma. A more comprehensive exploration of these proteins and their associated pathways and functions offers the prospect of elucidating the mechanistic underpinnings inherent in the documented relationship between sAAa and metabolic disorders.